Analisis Teologis Perempuan Kristen di Pandang dari Kisah Debora dan Ester - Rensiani Lebang Pasorong; Yehezkiel Siappa; Otniel Fradel Januar; Septian Rangga Rante Lembang; Ingrid Yuwiesia Allo Linggi (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2026)
This study explores the relevance of women’s position in leadership within the contemporary context by considering the roles of women throughout history as well as the values underlying perspectives on leadership in modern society. Through a critical analysis of biblical texts, particularly in the Old Testament, this journal seeks to understand how female figures in the Bible, namely Deborah, Ruth, and Esther, influence perceptions of women in leadership. The findings of this study provide profound insights into the relevance and challenges faced by women in pursuing leadership careers in the contemporary era. In the modern context, women still face a number of challenges that hinder their progress in attaining leadership positions. Some of these challenges include gender inequality. The importance of gender equality in the modern context can also be seen from the relevance previously mentioned regarding the position of women in contemporary leadership. This study highlights the importance of understanding and encouraging women’s participation in leadership as an integral part of creating a just, inclusive, and sustainable society. Gender equality is not only about providing equal rights to all individuals, but also about recognizing and appreciating the diverse contributions of all people, regardless of gender.